A comparative study of temporalis fascia grafting techniques in cortical mastoidectomy with type 1 tympanoplasty patients in tertiary care hospital - M., Gowrishankar; K., Athiyaman; V., Suresh; R., Gayathiri; S., Natarajan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Chronic otitis media is a highly prevalent middle ear disease in the developing countries which causes various pathological changes in the tympanic membrane and middle ear. Treatment of chronic otitis media involve medical and surgical methods. There are many surgical techniques followed regarding the grafts used, temporalis fascia remains the most commonly used. There are some studies debating the usefulness of dry grafts and wet grafts. Our study is aimed at comparing the both and evaluating the outcome. Methods: A prospective comparative study conducted in the department of Otorhinolaryngology and Head and Neck surgery, Government Stanley Medical College, Chennai, with 64 patients for the period of 1 year from July 2017 to June 2018. Results: Graft uptake of temporalis fascia in dry group is 93.8% and wet group has graft uptake of 87.5%, failure rate is low in dry group when compared with wet group. And also, this study showed higher graft uptake in small and medium sized perforation (95%) than the larger perforation (87.5%) and also there is no relationship between the duration of inactive stage and the graft uptake has been observed in our study. Conclusion: Temporalis fascia is a reliable graft material for reconstruction of tympanic membrane perforations. In our study dry graft has shown more success rate than the wet graft. Hearing improvement was the same in dry and wet group in which the grafts have been up taken well.